'No outlines': From dystopia to heterotopia in Howard Jacobson's J. (1st April 2016) - Gilbert, Ruth
This article suggests that a dystopian reading of Howard Jacobson's 2014 novel, J, is not necessarily the only way in which to reflect on both the inner and outer topographies of the narrative. In tilting the focus of enquiry, the article draws from Foucault's brief, but intriguing, thoughts on heterotopia. It suggests that this kind of heterotopian thinking potentially opens up a deconstructive questioning of terms such as utopia and dystopia. In particular, the article teases out some of the ways in which Jewishness intersects with these themes. The analysis focuses on the section towards the mid-point of J when the protagonists, Kevern and Ailinn, visit the capital city of a bleak new world. It is a profoundly dislocated and disconcerting space, described as 'a city seen through a sheet of scratched Perspex …. it had no outlines'. Within this distorted setting, Jacobson presents a sustained exploration of Jewishness, an identity that is placed, simultaneously, at both the centre and the edges of the text.